Liberty, Equality, Maternity. - Fell, Alison (Taylor and Francis, 2002)
"The concept of motherhood emerges strongly in the writings of Simone de Beauvoir, Violette Leduc and Annie Ernaux, whose work is examined here in the light of current debates about women's reproductive function and the longstanding glorification of the mere au foyer in France, driven by fear of a falling population. In this interdisciplinary study of twentieth-century French women's writing, Fell uncovers tensions at the heart of the literary critique. She shows these authors challenging the patriarchal view of motherhood as the sole justification for a woman's existence while at the same time confronting the conflict inherent in their relationship with their own mothers. A survey of theoretical and historical material demonstrates vividly that the changing concept of motherhood remains a problematic and highly contentious issue for French feminists, whether writing in 1940 or 1999."